Kyiv durind the Holodomor-genocide (1932-1933) - Ivanets, Andriy; Petrenko, Ivan (Ukrainian Peasant, 2021)
Introduction. The criminal policy of excessive grain procurement, which the communist totalitarian regime used as a weapon to subdue and destroy the Ukrainian nation, already in early 1932 led to large-scale famine and death rates in Ukraine, the Kuban and those regions of the Soviet Union where millions of Ukrainians lived compactly. Large masses of Ukrainians from rural areas, primarily from the Kyiv region, in 1932-1933 tried different ways and opportunities to reach Kyiv. In the big city, they hoped to survive themselves and with their children from starvation, as well as get a job at one of Kyiv’s many plants, fl eeing from collective farm slavery. However, the food and sanitary-epidemic situation in Kyiv was not much better than in the starving Ukrainian villages. Thousands of Ukrainians living in Kyiv were forced to starve and live in inhumane living conditions, replenishing the number of victims of the crime of the communist totalitarian regime every day. Purpose. The purpose of the article is to investigate the socio-economic, food, material, household, epidemic situations in Kyiv during the communist totalitarian regime’s genocide of Ukrainians in 1932-1933. Methods of the study. To achieve this goal, problem-chronological, historical-comparative, system-structural, logical-analytical and descriptive methods were used. Originality. Based on a wide range of eyewitness testimonies that survived the Holodomor-genocide in Kyiv, a large amount of published and archival documents, a comprehensive analysis of key aspects of life in Kyiv during the communist totalitarian regime’s genocide of Ukrainians in 1932-1933 was made for the fi rst time. Conclusion. Aiming to undermine the moral and psychological strength of the Ukrainian nation, its desire for national and state revival, the communist totalitarian regime committed genocide against Ukrainians, using artifi cially organized famine as the main instrument of the crime. The policy of excessive, criminal procurement of bread led to the Holodomor-genocide in Ukraine, the Kuban and other regions of the Soviet Union, where Ukrainians lived compactly. Exhausted by starvation, Ukrainians went to large industrial cities to escape from death and in hope to fi nd some food there. Kyiv was no exception in this context. During the Holodomor-genocide, thousands of Ukrainians died on its streets, thousands of children became homeless or were sent to Kyiv orphanages. In turn, famine, mass deaths and a terrible sanitary and epidemic situation provoked an outbreak of an epidemic of infectious diseases in Kyiv, which also caused many deaths